Romantic breakup distress and flourishing in students: The mediating role of self-compassion - Peña-Muñante, Gonzalo (2024)
When a relationship ends, it is essential to identify strategies that help people cope with the breakup, as this will condition their future well-being. The aim of this study was to explore the relationship between romantic breakup distress and flourishing, considering self-compassion as a mediator variable. A questionnaire was administered to 506 students of different educational levels (secondary and higher) and ages (15 to over 23 years old) to obtain information on study variables. Correlational and inferential analyzes were performed. The results indicated that the loss of intimacy was the main reason for the breakup. Furthermore, there were significant differences in distress according to the duration of the broken relationship, the status of the initiator of the breakup, and the current relationship. Finally, a significant indirect effect of distress on flourishing through self-compassion was found.